2012
DOI: 10.1186/1756-6614-5-1
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific regulation of response to thyroid hormone in aging

Abstract: BackgroundSimilar to other systems, the endocrine system is affected by aging. Thyroid hormone, the action of which is affected by many factors, has been shown to be associated with longevity. The most useful marker for the assessment of thyroid hormone action is TSH level. Although age and gender are believed to modify the pituitary set point or response to free thyroid hormone concentration, the precise age- and gender-dependent responses to thyroid hormone have yet to be reported.MethodsWe analyzed the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 20 publications
7
38
1
Order By: Relevance
“…TSH is involved in regulating the activity of triiodothyronine (T 3 ) and thyroxine (T 4 ) [5,6], which interact with energy expenditure [7,8] . Significant negative changes in resting energy expenditure (REE), adjusted for the fatfree mass (FFM), as a function of TSH around the normal range induced by varying daily T 4 doses were reported in 9 female patients aged 25-72 [9] .…”
Section: Introductionmentioning
confidence: 99%
“…TSH is involved in regulating the activity of triiodothyronine (T 3 ) and thyroxine (T 4 ) [5,6], which interact with energy expenditure [7,8] . Significant negative changes in resting energy expenditure (REE), adjusted for the fatfree mass (FFM), as a function of TSH around the normal range induced by varying daily T 4 doses were reported in 9 female patients aged 25-72 [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Morreale de Escobar et al [6] have reported that thyroid hormones as being critical regulatory molecules that played an important role in functioning and development of various organs of vertebrate body particularly normal brain functioning before and after birth and further it has been examined that these are Tyrosine based hormones that are partially composed of iodine and their deficiency enlarges the thyroid tissue which is known as simple goiter [7]. Suzuki et al [8] have examined that alteration in TSH and free thyroid hormones have been observed in gender and during aging. They have further investigated that in males the process of aging have restrained the free thyroid hormones concentration but have not influenced on the concentration of TSH.…”
Section: Journal Of Clinical Epigenetics Issn 2472-1158mentioning
confidence: 99%
“…The clinical examination report of thyroid function tests were collected from various laboratories of Islamabad. In a whole sample of population, 131 patients were designated as normal and 53 patients as hyperthyroid or hypothyroid according to the values of TSH levels [13]. The study has worked out to determine the statistical difference between normal and hyperthyroid and hypothyroid versus control group individuals.…”
Section: Methodsmentioning
confidence: 99%